Economic integration in the euro-mediterranean region - Rym Ayadi; Moez El Elj; Michael Gasiorek; Ahmed Farouk Ghoneim; Selen Guerin; Peter Holmes; Hammad Kassal; Javier Lopez Gonzalez; Mahmut Tekce (Center for Social and Economic Research (CASE), 2009)
This study evaluates the effects of the current Euro-Mediterranean Free Trade Agreement for the EU and the Mediterranean region, in order to assist policy makers in defining the next steps in the Euro-Mediterranean Road map till 2010 and beyond. It provides quantitative, qualitative and sectoral assessment of the impacts of the Euro-Mediterranean FTA on trade and investment, points out the partnerships' strengths and weaknesses and provides policy recommendations with the view of realizing a goal of a well functioning free trade area in the future. The focus of the study is on Egypt, Israel, Jordan, Morocco, and Tunisia (MED5). [...]
Keywords: F15; M38; P33; 330; EU; mediterranean; regional integration; non-tariff barriers; international trade; investment; business perception survey; Regionale Wirtschaftsintegration; Regionale Wirtschaftsintegration; Freihandelszone; EU-Staaten; Ägypten; Israel; Jordanien; Marokko; Tunesien; Mittelmeerraum